2022
DOI: 10.3389/fimmu.2022.864007
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin and Related Peptide Hormones: Candidate Anti-Inflammatory Therapy in Early Stages of Sepsis

Abstract: Sepsis is a potentially life-threatening systemic inflammatory syndrome characterized by dysregulated host immunological responses to infection. Uncontrolled immune cell activation and exponential elevation in circulating cytokines can lead to sepsis, septic shock, multiple organ dysfunction syndrome, and death. Sepsis is associated with high re-hospitalization and recovery may be incomplete, with long term sequelae including post-sepsis syndrome. Consequently, sepsis continues to be a leading cause of morbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 219 publications
0
14
0
Order By: Relevance
“…Thus, it has been reported that OXT blocks the activation of inflammatory cells of the immune system, decreases cytokine levels and microglial activation in the central nervous system, decreases ischemia-reperfusion inflammation in the cardiovascular and musculoskeletal systems, lowers inflammatory cytokines in the gastrointestinal system, protects against LPSinduced acute lung injury, and decrease inflammation in adipocytes and in pyelonephritis. 11,14,[29][30][31] We have also demonstrated that OXT prevents alveolar bone loss. Our result is consistent with the findings that the stimulation of OXTR present in osteoclasts results in an inhibited bone resorption, 32 suggesting that OXT contributes to bone protection and/or regeneration in gingival tissues.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Thus, it has been reported that OXT blocks the activation of inflammatory cells of the immune system, decreases cytokine levels and microglial activation in the central nervous system, decreases ischemia-reperfusion inflammation in the cardiovascular and musculoskeletal systems, lowers inflammatory cytokines in the gastrointestinal system, protects against LPSinduced acute lung injury, and decrease inflammation in adipocytes and in pyelonephritis. 11,14,[29][30][31] We have also demonstrated that OXT prevents alveolar bone loss. Our result is consistent with the findings that the stimulation of OXTR present in osteoclasts results in an inhibited bone resorption, 32 suggesting that OXT contributes to bone protection and/or regeneration in gingival tissues.…”
Section: Discussionmentioning
confidence: 68%
“…[10][11][12] It has been reported the anti-inflammatory effects of OXT in the cardiovascular, gastrointestinal, endocrine, genitourinary, and central nervous systems. 11 OXT acts via its receptor (OXTR), which belongs to the heptahelical G protein-coupled receptor family, that has been detected in a broad diversity of cells and particularly in immune cells like neutrophils, macrophages, and lymphocytes. 10,13 Thus, OXT reduces expression levels of proinflammatory mediators and cytokines in cultured macrophages and endothelial cells 14 and attenuates the overactivation of microglial cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that certain anti-inflammatory drugs have anti-depressive effects [122] . Multiple studies have demonstrated significant anti-inflammatory effects of OXT in various diseases and systems, including the central nervous system, cardiovascular, lung, intestine, and urinary [160] , [161] . Oxytocin receptor (OXTR) is widely expressed in the hypothalamus, pituitary gland, adrenal gland [40] , as well as in a variety of immune elements such as microglia, astrocytes, and thymus [9] , all of which are affected in MDD.…”
Section: Oxt and Immune System In Mddmentioning
confidence: 99%
“…From the previously mentioned research, is it evident that although there is a potential for the use of oxytocin into COVID-19 patients, animal studies are needed to explore oxytocin treatment on these patients. In an earlier study in mice [ 170 ] ( Table 1 ) and in other studies presented in a review on the treatment of sepsis, among other diseases [ 210 ] OXT and related peptides might have a therapeutic role. Signs of multi-organ injury typical of sepsis occur in approximately 2–5% of COVID-19 patients 8–10 days post-infection, hence OXT potentially could alleviate this complication [ 211 ].…”
Section: Use Of Oxytocin In Dysfunctional Conditionsmentioning
confidence: 99%